CAMELS & ALTMAN ZETA : BANK OCBC NISPSEBELUM DAN SESUDAH AKUISISI - MIFTACHUL ILMI, SEFINDI (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :This research aims to determine the financial performance of OCBC NISP before and after acquisition. Measure instruments used in this research is ALTMAN ZETA and CAMELS. Altman Zeta used for bankruptcy prediction. CAMELS used for healthy bank. This research used paired sample t-test to compare the financial performance beforeacquisition of Bank NISP and Bank OCBC NISP after acquisition. Altman Zeta was significant differences before and after acquisition, because Zeta from OCBC NISP improved performance after acquisition. CAMELS method, component ?of 6 there is only one component that has significant differences in financial performance declined trend after the acquisition is shown from the calculation of BOPO ratio due to adaptation process of the two banks, so that operating income increased but followed by post-acquisition operating costs also increased so that the ratio BOPO experiencing declining trend. Based on this research, Altman Zeta and CAMELS showed that acquisition process has been successful. Keywords: financial performance, acquisition, altman zeta, and CAMELS.